Two decades of research on waste management in the circular economy: Insights from bibliometric, text mining, and content analyses. (10th September 2021) - Ranjbari, Meisam; Saidani, Michael; Shams Esfandabadi, Zahra; Peng, Wanxi; Lam, Su Shiung; Aghbashlo, Mortaza; Quatraro, Francesco; Tabatabaei, Meisam
Abstract: Achieving environmental sustainability and transition from a linear economy to a circular economy (CE) highly relies on effective waste management (WM) and how waste is treated as a potential future resource. This research aims to provide an inclusive map of the scientific background of WM in the CE context over the last two decades from 2001 to 2020 to identify its salient research themes and trends, main characteristics, evolution, and potentially valuable directions for future studies. To achieve that, the following research questions were addressed by applying a mixed-method approach including bibliometric, text mining, and content analyses: (i) how has the field of WM research evolved within the CE domain? (ii) what are the salient research themes and trends of WM in the CE? and (iii) what are the possible directions for future research on WM within the CE context? As a result, the synthesized bibliometric networks were constructed and analyzed for a total of 962 journal articles extracted from the Web of Science database to visualize the main body of literature. Consequently, the seven major research themes of WM in the CE context were identified as follows: (1) bio-based WM; (2) CE transition; (3) electronic waste; (4) municipal solid waste; (5) environmental impacts and lifecycle assessment; (6) plastic waste; and (7) construction and demolition WM. The provided inclusive research landscape of WM systems, and its prominent highlight patterns can serve as a base for a real-time guideline to lead further research areas and as a tool to support WM policy-makers and practitioners to support the CE transition (which aims to minimize the waste generation). Finally, the future research directions to better position WM research activities within the CE context as a waste minimization approach are provided. Graphical abstract: Image 1 Highlights: The literature on waste management (WM) in the circular economy (CE) was mapped. Bibliometric networks were constructed for a total of 962 journal articles. The seven major research themes of WM in the CE context were presented. Directions for future research on WM towards the CE transition were proposed.